Gender diversity in academic publishing—comment on Galak and Kahn (2021) - Wiebke I. Y. Keller; Franziska Müller; Malik Stromberg; Dominik Papies (Marketing Letters, 2021)
Galak and Kahn (Marketing Letters, 2021) report that females and underrepresented minorities face a less favorable organizational climate within academic marketing as compared to their respective counterparts. We complement this perspective by assessing the extent to which a gender gap is detectable in academic journal publications in marketing. To this end, we collect a data set which covers all publications of a broad range of peer-reviewed academic journals in business, including marketing, across two decades. We then develop an algorithm that allows us to determine the authors' gender. We use these data to study a potential gender gap in academic marketing journals. Results indicate that a gender gap in academic publishing in marketing is present and substantial, although it has been declining over time. At the same time, it continues to be~particularly visible in the most prestigious journals. While marketing is still far from being a role model, the gender gap is smaller in marketing compared to other fields in business. Our analysis complements the findings by Galak and Kahn (Marketing Letters, 2021) by showing that female scholars do not only experience an unfavorable organizational climate, but they are also underrepresented in academic marketing journals.
Keywords: 380; Gender gap; Academic publishing